Effect of annealing temperature on the crystallization of hematite-alumina (Fe2O3-Al2O3 ) nanocomposite and its influence in EOR application - Soleimani, H. (Trans Tech Publications Ltd, 2014)
Usage of magnetic materials is not unusual in oil and gas research, specifically in enhanced oil recovery (EOR) where various magnetic micro- and nanoparticles were used to enhance sweep efficiency, reducing interfacial tension and heat generation. Magnetic nanoparticles which are activated by a magnetic field are anticipated to have the ability to travel far into the oil reservoir and assist in the displacement of the trapped oil. In this work, magnetic Fe2O3-Al2O3 nanocomposite was synthesized and characterized for its morphological, structural and magnetic properties. At an annealing temperature of 900Â°C, this nanomaterial starts to exhibit magnetization as the composite structure crystallizes to the stable Fe2O3 and Al2O3. Subsequently, dispersion of the 0.01 wt Fe2O3-Al2O3 nanocomposite in distilled water was used for displacement tests to validate its feasibility to be applied in EOR. In the displacement test, the effect of electromagnetic waves on the magnetization of Fe2O3-Al2O3 nanofluid was also investigated by irradiating a 13.6 MHz square wave to the porous medium while nanofluid injection is taking place. In conclusion, an almost 20 increment in the recovery of oil was obtained with the application of electromagnetic waves in 2.4 pore volumes (PV) injection of Fe2O3-Al2O3 nanofluid. Â© (2014) Trans Tech Publications, Switzerland.